Diversity of Grasshopper (Hexapoda: Orthoptera) in the Conservation Area of Kerandangan Natur Park, Senggigi, West Lombok - Ilhamdi, Mohammad Liwa; Syazali, Muhammad; Rizki, Baiq Febrian Sari (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
The Kerandangan TWA conservation area has high biodiversity, but much of it is unknown, including grasshoppers. This research aims to analyze the diversity of grasshoppers in the area. Grasshopper samples were collected on two transects determined purposively. This collection was carried out over two months, namely October to November 2022. Data on species and numbers were analyzed descriptively. This analysis includes abundance, richness index, diversity index, and species evenness index. Our findings show that there are 8 species of grasshoppers from the families Acrididae, Pyrgomorphidae, Catantopidae, and Tettigoniidae. The most abundant species was Stenocatantops splendens, whose proportion was 66.67%. The species richness, diversity, and evenness indexes were 2.06, 1.27, and 0.61, respectively. This shows that grasshopper biodiversity in Kerandangan TWA is relatively low. However, it must be conserved because of its essential role in maintaining regional ecological processes.